2017
DOI: 10.1177/1553350617690308
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Laparoscopic Inguinal Hernioplasty Versus Conventional Laparoscopic Inguinal Hernioplasty

Abstract: Our meta-analysis has shown that inguinal hernia repair using SILH is as safe as CLH. However, based on our evidence, we currently believe that SILH is not an efficacious surgical alternative to CLH for inguinal hernias due to the fact that it does not provide significant benefit in postoperative pain and cosmetic outcomes. However, large-scale, well-designed, and multicenter studies will be needed to further confirm the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Very limited information only could be found on the transabdominal preperitoneal (TAPP) approach. The literature search identified four RCTs [144147] (n = 398) on this topic and one meta-analysis [148]. Only three of the four RCTs were included in this meta-analysis as one of the trials was published later.…”
Section: Resultsmentioning
confidence: 99%
“…Very limited information only could be found on the transabdominal preperitoneal (TAPP) approach. The literature search identified four RCTs [144147] (n = 398) on this topic and one meta-analysis [148]. Only three of the four RCTs were included in this meta-analysis as one of the trials was published later.…”
Section: Resultsmentioning
confidence: 99%
“…According to Lai et al , the operative time for unilateral repair took significantly longer with LESS TEP than with conventional TEP ( P = 0.01), but bilateral TEP repairs took similar amounts of time. The Luo et al review reported that both unilateral and bilateral LESS TEP repairs required a longer operative time than their conventional counterparts ( P = 0.001 and P = 0.016, respectively), but were associated significantly less postoperative pain with LESS TEP technique (POD) 7 ( P = 0.021) . Neither study found a significant difference in incidence of conversion, development of complications, length of hospital stay, duration of recovery, and incidence of recurrence between the LESS and conventional TEP.…”
Section: Current Evidencementioning
confidence: 99%
“…Five meta‐analyses and reviews were found (Table ). Three studies compared the outcomes of various LESS and conventional LIHR , and the other two studies compared LESS and conventional TEP .…”
Section: Current Evidencementioning
confidence: 99%
See 2 more Smart Citations